Growth performance and nutrient utilization indices of African Catfish (Clarias gariepinus BURCHELL, 1822) Fingerlings fed graded levels of Calabash Seed Cake - Jibrin, H.; Magawata, I.; Argungu, L. A.; Na-Allah, Y.; Abubakar, M. Y; Mohammed, A. (ADAN JOURNAL OF AGRICULTURE, 2026)
The study evaluated the potential of calabash seed cake as a replacement for groundnut cake in the diet of Clarias gariepinus fingerlings. Five isonitrogenous (40% crude protein) and isocaloric (3,260.20 kcal kg⁻¹ metabolizable energy) diets were formulated in which boiled seed cake replaced groundnut cake at 0, 25, 50, 75, and 100%. A total of 300 Clarias gariepinus fingerlings, average weight 2.64 g and average length 4.76 cm were allocated to fifteen experimental tanks, with 20 fish per tank and three replicates per treatment, reared for a period of ten weeks during which growth and nutrient utilization were evaluated. The survival rate (98.33 ± 1.67%) was significantly higher (p < 0.05) in fish fed diet D (75% Calabash seed cake) than in the other four treatments. Survival did not differ significantly (p > 0.05) among diets B (25%), C (50%), and E (100%), but these were significantly higher (p < 0.05) than the control diet (0% Calabash seed cake), which had the lowest survival (83.33±4.41%). The highest mean weight gain (42.13 ± 1.01 g), percentage weight gain (1,601.47 ± 10.42%), and percentage length increase (258.00 ± 7.17%) were recorded in fish fed the diet containing 25% calabash seed cake. However, specific growth rate and condition factor did not differ significantly among treatments (P > 0.05). There were no significant differences in feed conversion ratio (FCR) and protein efficiency ratio (PER) across the graded levels of calabash seed cake (CSC) diets; however, the 25% CSC diet provided the best gross feed conversion efficiency (GFCE) and apparent net protein utilization (AppNPU). It is recommended that boiled seed cake be included in the feed of Clarias gariepinus at 25% for optimum growth performance and feed digestibility. Field experiments, particularly in semi-intensive earthen pond systems, are suggested. Further studies involving boiled seed cake with other cultured species are highly recommended.